Research on European capacity cost recovery mechanism and its experience to China's power market construction. Issue 4 (May 2021) - Xing, Yuhui; Zhang, Maolin; Liu, Xiangrui; Chen, Qinggui; Mu, Chunfeng; Wang, Bangcan
Abstract: This paper makes an in-depth study of generation capacity cost recovery issues that have been, or are being faced, in European countries and summarizes its experience to China during the construction of competitive power markets. Firstly, the paper explains the idea and principle of capacity cost recovery mechanisms in EU, which are policy instruments to ensure adequate investment in generation capacity, then analyses the obstacles to the realization of capacity cost recovery in the energy-only market. Then, the paper divides the European capacity cost recovery mechanism into five categories: strategic reserve, capacity obligation, capacity auction, reliability option and capacity payment, and expounds the operation flow of the mechanisms respectively in detail. Thirdly, the paper studies the possible impact of the capacity cost recovery mechanism on the electricity market. Finally, the paper summarizes the practical experience of European capacity cost recovery mechanisms and lay a foundation for the design of generation capacity cost recovery mechanism in China.